2013
DOI: 10.1080/00036846.2013.835483
|View full text |Cite
|
Sign up to set email alerts
|

Chinese resource demand and the natural resource supplier

Abstract: This paper provides empirical evidence on the effects of Chinese resource demand on the resource rich natural resource supplier using the example of Australia. A structural VAR model is used to examine the effects of Chinese resource demand, commodity prices and foreign output on the macroeconomy with a formally specified mining and resources exports sector. The key findings of the paper are that shocks to Chinese demand and commodity prices result in a sustained increase in commodity prices and mining investm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…Those that have analysed the issue, have typically employed a structural vector autoregression (SVAR), including only a single sector in the non‐resource economy, such as manufacturing or domestic output, see, for example, Hutchison (), Bjørnland () and Dungey et al . (), or a panel data approach studying common movements in manufacturing across numerous countries, see, for example, Ismail (). The overall conclusion has been that effects of, say, mining or petroleum investment on domestic output are small, c.f., Dungey et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Those that have analysed the issue, have typically employed a structural vector autoregression (SVAR), including only a single sector in the non‐resource economy, such as manufacturing or domestic output, see, for example, Hutchison (), Bjørnland () and Dungey et al . (), or a panel data approach studying common movements in manufacturing across numerous countries, see, for example, Ismail (). The overall conclusion has been that effects of, say, mining or petroleum investment on domestic output are small, c.f., Dungey et al .…”
mentioning
confidence: 99%
“…The overall conclusion has been that effects of, say, mining or petroleum investment on domestic output are small, c.f., Dungey et al . () or Bjørnland (). However, neither of these approaches accounts for cross‐sectional co‐movement of variables and sectors within a country.…”
mentioning
confidence: 99%
“…This article further contributes to the literature on the spillover effects of Chinese activity on small open economy commodity exporters. Dungey et al (2014) found that shocks to Chinese resource demand and commodity prices led to lower Australian output after the first year due to falls in non-resource sector output, which was not offset by an increase in the resource output sector, which is consistent with the symptoms of Dutch disease. Subsequently, Dungey et al (2017) found reduced evidence of Dutch disease in the Australia economy in the aftermath of the end of the commodity price boom.…”
Section: Introductionmentioning
confidence: 58%
“…The emergence of China as an economic powerhouse has contributed to the rapid transformation of the structure of the global economy (Jenkins, 2014). In particular, the unprecedented demand for natural resources for purposes of industrialization and urbanization has led to potentially substantial spillover effects for commodity-exporting countries (Cesa-Bianchi et al, 2012;Dungey et al, 2014Dungey et al, , 2017. The empirical evidence suggests that the impacts of Chinese economic shocks on a typical Latin American economy have tripled since mid-1990(Cesa-Bianchi et al, 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation